PERFORMANCE EVALUATION OF SEWAGE TREATMENT PLANT USING BIOCHIP MEDIA IN MBBR TECHNOLOGY : CASE STUDY “X GARMENT, CENTRAL JAVA - Yusrina, Afifah; Ardhianto, Rachmad; Darojat, Khumaidah; Rahman, Arief (Lingkar: Journal of Environmental Engineering, 2024)
“X” garment industry’s Sewage Treatment Plant (STP) was built to treat domestic wastewater with an inflow capacity of 500 m3/day. The main principle of the STP technology is an attached growth process with Moving Bed Biofilm Reactor (MBBR) technology using biochip media. Wastewater treated at the STP must meet the water quality standards of Ministry of Environment and Forestry Regulation 68 of 2016 before being discharged into water bodies. Therefore, this research aimed to evaluate the “X” garment industry’s STP performance. Wastewater sampling was carried out at the inlet and outlet of STP. Water quality parameters analyzed included pH, BOD, COD, TSS, oil and grease, ammonia, and total coliforms. The removal efficiency value is obtained from the calculation of sampling results. The analysis showed that all treated water parameters met the water quality standards throughout the research period. Hence, the average removal efficiency value at the STP for each parameter was above 90%.